Design Science Research para projetar um modelo conceitual acerca de informações prosopográficas sobre políticos. - Barroso Jr., José S.; Pimentel, Mariano; Nunes, Vanessa; Cappelli, Claudia (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
The growing demand for information about politicians and the speed with which news is propagated by media and social networks reveals in contemporary times a more participatory view of the citizen in politics and social control in government actions. Speculation about information about politicians and their respective parties have become more constant, such as in electoral periods, investigations on processes, journalistic interest, etc. This can be observed during the electoral period of 2018 in which the search for information about the candidates and their respective parties was notorious. Given that information transparency is paramount for a democratic regime, the organization and consolidation of data from official sources is a reliable tool for consultation and dissemination of knowledge. According to this period, this work sought to understand some cognitive models that explain electoral behavior, which led to the investigation of factors that influence the decision to vote. The observed cognitive models indicate some attitudes, opinions, satisfactions, events and government assessments that interfere to some degree in the choice of vote, approval or disapproval for some purpose. Among the factors of influence observed, there are prosopographic information, which deals with the biography of politicians, and which are available in the various transparency portals. However, the data contained in these platforms are not organized in such a way as to make the information more intelligible and more reliable to the citizen. In this sense, this research is interested in the prosopographic information content, which would be better evaluated if the data of the politicians were organized according to a conceptual model of knowledge. The methodological approach adopted in this research is the Design Science Reserch (DSR), which directs the construction of an artifact in a given context, whose theoretical conjectures are based on the search and production of knowledge. As a result, research contributes to the knowledge base, as it discusses the evolution of cognitive models and through the design of the artifact, delivers reliable and relevant information about the life of a politician.